Alzheimer's Disease: Mechanism and Approach to Cell Therapy - Amemori, Takashi; Jendelova, Pavla; Ruzicka, Jiri; Urdzikova, Lucia Machova; Sykova, Eva (International journal of molecular sciences, 2015)
Alzheimer's disease (AD) is the most common form of dementia. The risk of AD increases with age. Although two of the main pathological features of AD, amyloid plaques and neurofibrillary tangles, were already recognized by Alois Alzheimer at the beginning of the 20th century, the pathogenesis of the disease remains unsettled. Therapeutic approaches targeting plaques or tangles have not yet resulted in satisfactory improvements in AD treatment. This may, in part, be due to early-onset and late-onset AD pathogenesis being underpinned by different mechanisms. Most animal models of AD are generated from gene mutations involved in early onset familial AD, accounting for only 1% of all cases, which may consequently complicate our understanding of AD mechanisms. In this article, the authors discuss the pathogenesis of AD according to the two main neuropathologies, including senescence-related mechanisms and possible treatments using stem cells, namely mesenchymal and neural stem cells.
Keywords: mutace; Stem Cell Transplantation; Animals; Stem Cells; věk při počátku nemoci; amyloid-β; Amyloid beta-Peptides; tau Proteins; Aging; mesenchymal stem cells; energetický metabolismus; neuroglie; lidé; Immunotherapy; amyloidní beta-protein; neural stem cells; transplantace kmenových buněk; kmenové buňky; Energy Metabolism; Mutation; Cell- and Tissue-Based Therapy; Alzheimer’s disease; modely nemocí na zvířatech; imunoterapie; amyloidní plaky; Alzheimer Disease; stárnutí; Neuroglia; Disease Models, Animal; Plaque, Amyloid; Alzheimerova nemoc; buněčná a tkáňová terapie; Age of Onset; zvířata; Tau; proteiny tau; Humans